Single-Bundle vs Double-Bundle (Anatomical) Reconstruction of the Thumb Ulnar Collateral Ligament: Biomechanical Study. (July 2019) - Jimenez, Megan L.; Hioe, Stephen D.; Kachooei, Amir R.; Shearin, Jonathan W.; Jones, Christopher M.; Rivlin, Michael
Background: The goal of this study is to compare the biomechanical properties of anatomic (double-bundle) versus single-bundle reconstruction of the thumb metacarpophalangeal (MCP) joint ulnar collateral ligament (UCL) in a cadaveric model.Methods: Twelve fresh frozen cadaver hands were randomly assigned to single- or double-bundle reconstruction groups using a palmaris longus autograft and tenodesis screws. Two blinded examiners performed mechanical testing and measurements using fluoroscopic imaging. We evaluated MCP joint congruence and angle in the coronal plane at 0°, 30°, and 60° of flexion with valgus loads of 1.36 and 2.72 kg. Maximum MCP flexion and extension with a 0.45 kg load was also measured.Results: There was no significant difference between single- versus double-bundle reconstruction in ulnar congruence or MCP angle. With varying amounts of flexion, there was no significant difference in MCP valgus angle between the 2 techniques, suggesting comparable joint congruity and coronal MCP angle along the arc of thumb MCP motion.Conclusions: Single- and double-bundle UCL reconstructions of the thumb MCP joint have comparable biomechanical properties in regard to joint congruity under valgus load.